The Relationship Between Risk Factors and the Incidence of Stunting in Children Aged 24-59 Months - Rahma Kusuma Dewi; Dhita Kris Prasetyanti; Meirna Eka Fitriasnani; Lindha Sri Kusumawati (STRADA : Jurnal Ilmiah Kesehatan, 2024)
Stunting occurs due to malnutrition during pregnancy and early childhood which results in stunted physical growth and brain development of children which can have an impact on the quality of life of children in the future. This study aims to examine the relationship between risk factors and the incidence of stunting in children aged 24-59 months in the work area of ​​the Pesantren I Health Center, Kediri City in 2023. A total of 189 toddler samples were randomly selected and the data were analyzed using the Chi-Square test. Mothers with low levels of education have a higher risk of having children with stunting (RR 0.3, p <0.05), while medium and high levels of education are not significantly related.